Compact Conformal Slot Antenna for Hyperthermia Applications - Singh S.; Singh D.; Singh S.P. (My University, 2025)
In this paper, a new compact conformal slot antenna having the highly focused beam which is in close proximity with muscle medium is presented for hyperthermia application. A simple 50 Ω microstrip line is used to excite the proposed conformal antenna. The input reflection coefficient of the antenna and hyperthermia assurance parameters viz. penetration depth, effective field size and temperature distributions in the muscle medium are evaluated for different antenna curvature (curvature of the applicator is alike to the bio-model). The simulation study reveals the effectiveness of the proposed antenna for hyperthermia treatment of abdominal tumors. © 2019 IEEE.